2019
DOI: 10.1177/0891988719882093
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Sustained Attention Response Task to Quantify Cognitive Fluctuations in Dementia With Lewy Bodies

Abstract: Cognitive fluctuations (CFs) are a core diagnostic feature of dementia with Lewy bodies (DLB). Detection of CF is still mostly based on subjective reports from the patient or informant; more quantitative measures are likely to improve the accuracy for the diagnosis of DLB. The purpose of the current study is to test whether performance on the Sustained Attention Response Task (SART) could distinguish those patients with DLB with and without CF. Twenty-four patients with DLB were tested on the SART and performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…In addition to the scales described above, the use of neuropsychological tests that provide information on the variability of response times may also be considered as a surrogate marker for cognitive fluctuations. Using computerized batteries, such as the sustained attention response task, choice reaction time, simple reaction time, or digit vigilance, the degree of variability in the response has been shown to correlate with performance in clinical cognitive fluctuation scales without being affected by motor deficits [ 126 , 128 ]. However, whilst these tools show promise in the evaluation of response to medications impacting cognitive fluctuations, they have yet to be validated.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the scales described above, the use of neuropsychological tests that provide information on the variability of response times may also be considered as a surrogate marker for cognitive fluctuations. Using computerized batteries, such as the sustained attention response task, choice reaction time, simple reaction time, or digit vigilance, the degree of variability in the response has been shown to correlate with performance in clinical cognitive fluctuation scales without being affected by motor deficits [ 126 , 128 ]. However, whilst these tools show promise in the evaluation of response to medications impacting cognitive fluctuations, they have yet to be validated.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a high occurrence of cognitive fluctuations was also associated with poor MR performance. The basis of this observation is less clear, as patients with severe fluctuations have also been shown to perform poorly on attentional tasks 45 . Thus, it may be that patients with poor attention or concentration might struggle to perform MR.…”
Section: Discussionmentioning
confidence: 99%
“…The SART is a task of attention that probes the core feature of cognitive fluctuations (CF) by presenting the subject with a series of numbers between 1 and 9. Patients are required to press a button when any number is presented but withhold their response when the number “3” is displayed (for full description, see Phillips et al [ 43 ]). The number of missed responses and variance in response time (RTSD) have been shown to correlate with CF in DLB patients [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients with iRBD underwent detailed longitudinal assessment at the ForeFront Parkinson’s Disease Research Clinic at the Brain and Mind Centre, University of Sydney. They also completed the Sustained Attention Response task (SART), which has been found to be sensitive to CF in DLB patients [ 43 ], the Mental Rotation (MR) task, a visuospatial task that has also been shown to be impaired in DLB patients [ 44 ] and the Bistable Percept Paradigm (BPP) which is sensitive to VF in PD [ 45 ] and DLB patients [ 46 ]. These three tasks were chosen for two reasons: previous studies they have shown them to be sensitive to symptoms (CF, VF and visuospatial impairment) in DLB patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation